Vitrification Increased Vacuolization of Human Spermatozoa: Application of MSOME Technology - S Taherzadeh; MA Khalili; A Agha-Rahimi; F Anbari; Sh Ghazali; G Macchiarelli (JRI, 2017)
Background: Sperm vitrification is a technique of ice and cryoprotectant free cryopreservation by direct plunging of sperm suspension into liquid nitrogen (LN2). The aim of this study was to investigate the influence of cryoprotectant free-vitrification on human sperm fine structure by MSOME technology and the fertility potential by zona binding assay (ZBA). Methods: 20 normo-ejaculates were prepared by swim up technique, and supernatants were divided into two parts of fresh and vitrified groups. For vitrification, sperm was dropped into LN2. Sperm motility, morphology, viability and MSOME were evaluated for each sample. In MSOM morphologically normal sperm (class 1), ≤2 small vacuoles (class 2), and one large vacuole or >2 small vacuoles (class 3) were evaluated. Also, fertility potential was evaluated by zona binding assay. Data was analyzed using paired t-test or Willcoxon’s test and p-value <0.05 was considered significant. Results: Vitrification significantly reduced both progressive motility, viability and morphology. Also, normal morphology of spermatozoa decreased significantly after vitrification. In MSOME evaluation, normal motile spermatozoa (Class 1) decreased from 23.00±12.44 to 16.00.56±10.79 after vitrification (p=0.008). Although spermatozoa classes 2 and 3 were increased, the difference was not significant. Moreover, fertility potential of motile spermatozoa was reduced after vitrification (9.0±13.87 vs. 13.40±22.73; p=0.07). Conclusion: Vitrification increased the rate of vacuolization in motile sperm head. Therefore, MSOME technology is recommended for assessment of sperm fine morphology in ICSI program used cryopreserved spermatozoa.